PENGEMBANGAN JURNAL ILMIAH ONLINE PADA SEKOLAN TINGGI TEOLOGIA BETHEL MEDAN - Paska Marto Hasugian (Sean Institute, 2023)
This community service aims to document the process of developing an online scientific journal as an effort to expand the impact of academic knowledge from Bethel College of Theology (STT) in Medan. Through a collaborative approach, this research involved faculty members and administrative staff in developing an effective and accessible online scientific journal platform. The development process included needs analysis, interface design, technical development, and pilot testing and evaluation. The outcome of this service was the launch of a scientific journal platform that facilitates publication, peer-review, and knowledge exchange digitally. It is hoped that this initiative will enrich the quality of research and scientific understanding among students, lecturers, as well as the academic community, while making a sustainable contribution to the development of knowledge in the field of theology and religion.